2007
DOI: 10.1111/j.1463-1326.2007.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Transferring to insulin detemir from NPH insulin or insulin glargine in type 2 diabetes patients on basal‐only therapy with oral antidiabetic drugs improves glycaemic control and reduces weight gain and risk of hypoglycaemia: 14‐week follow‐up data from PREDICTIVE™

Abstract: These results indicate that in type 2 diabetes, transferring from other basal insulins to insulin detemir in combination with OADs was associated with improvements in glycaemic control, which were accompanied by a reduced risk of hypoglycaemia and a reduction in body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 15 publications
(23 reference statements)
3
34
1
Order By: Relevance
“…Fourteen weeks after the switch to detemir, mean body weight was significantly reduced in patients previously using both NPH insulin (-0.7 kg; P<0.01) and insulin glargine (-0.5 kg; P<0.05). 102 Other studies have documented weight increases or weight stasis after treatment with glargine, although the weight increases, when observed, tended to be less than those occurring with NPH insulin. [103][104][105][106][107][108][109][110][111][112][113][114] The mechanisms behind the weight-sparing trait of insulin detemir have yet to be fully clarified.…”
Section: Weight Gainmentioning
confidence: 99%
“…Fourteen weeks after the switch to detemir, mean body weight was significantly reduced in patients previously using both NPH insulin (-0.7 kg; P<0.01) and insulin glargine (-0.5 kg; P<0.05). 102 Other studies have documented weight increases or weight stasis after treatment with glargine, although the weight increases, when observed, tended to be less than those occurring with NPH insulin. [103][104][105][106][107][108][109][110][111][112][113][114] The mechanisms behind the weight-sparing trait of insulin detemir have yet to be fully clarified.…”
Section: Weight Gainmentioning
confidence: 99%
“…Randomized controlled trials have demonstrated that insulin detemir is an effective OD basal insulin for use in patients with T2DM 8,12 , with observational data further supporting its effectiveness in many patients 18,20 . PREDICTIVE* is a large, observational study of the empirical use of insulin detemir in patients with type 1 or type 2 diabetes in a representative clinical setting.…”
Section: Introductionmentioning
confidence: 98%
“…This was also observed in European cohort of PREDICTIVE study in T2DM patients, where switching to detemir from prior insulins (glargine and NPH) resulted in more pronounced effect, with HbA1c reductions up to 0.6%. 25 The reduced subject variability, improved diabetes care, and continued follow-up also resulted in a better compliance, thus achieving better glycemic control.…”
Section: Discussionmentioning
confidence: 99%